Tracking Immunity: An Increased Number of COVID-19 Boosters Increases the Longevity of Anti-RBD and Anti-RBD-Neutralizing Antibodies - Ching-Wen Hou; Stacy Williams; Veronica Boyle; Alexa Roeder; Bradley Bobbett; Izamar Garcia; Giavanna Caruth; Mitch Magee; Yunro Chung; Douglas F. Lake; Joshua LaBaer; Vel Murugan (Vaccines)
Background/Objectives: Since the World Health Organization declared COVID-19 a pandemic in March 2020, the virus has caused multiple waves of infection globally. Arizona State University (ASU), the largest four-year university in the United States, offers a uniquely diverse setting for assessing immunity within a large community. This study aimed to test our hypothesis that an increased number of exposures to SARS-CoV-2 RBD through vaccination/boosters/infection will increase SARS-CoV-2 antibody seroprevalence by increasing the longevity of anti-RBD and anti-RBD-neutralizing antibodies. Methods: A serosurvey was conducted at ASU from 30 January to 3 February 2023. Participants completed questionnaires about demographics, respiratory infection history, symptoms, and COVID-19 vaccination status. Blood samples were analyzed for anti-receptor binding domain (RBD) IgG and anti-nucleocapsid (NC) antibodies, offering a comprehensive view of immunity from both natural infection and vaccination. Results: The seroprevalence of anti-RBD IgG antibodies was 96.2% (95% CI: 94.8–97.2%), and 64.9% (95% CI: 61.9–67.8%) of participants had anti-NC antibodies. Anti-RBD IgG levels correlated strongly with neutralizing antibody levels, and participants who received more vaccine doses showed higher levels of both anti-RBD IgG and neutralizing antibodies. Increasing the number of exposures through vaccination and/or infection resulted in higher and long-lasting antibodies. Conclusions: The high levels of anti-RBD antibodies observed reflect substantial vaccine uptake within this population. Ongoing vaccination efforts, especially as new variants emerge, are essential to maintaining protective antibody levels. These findings underscore the importance of sustained public health initiatives to support broad-based immunity and protection.